Introduction, 'Beyond Open: Implementing Social Scholarship' - Alyssa Arbuckle; Luis Meneses; Ray Siemens (KULA, 2019)
On January 10–11 2018 the Implementing New Knowledge Environments (INKE) Partnership held Beyond Open: Implementing Social Scholarship, a gathering that brought ~60 researchers, students, librarians, and academic-aligned groups together on the topics of scholarly communication, open access, and community engagement. This special issue is a snapshot of the event proceedings, organized around open social scholarship theory, infrastructure, and projects. Wide-ranging in content, the authors included here all come together under the banner of imagining more social, community-minded applications for academic work.